Selective Membrane Redistribution and Depletion of Gα(q)-Protein by Pasteurella multocida Toxin - Clemons, Nathan C. (Toxins (Basel), 2016)
Pasteurella multocida toxin (PMT), the major virulence factor responsible for zoonotic atrophic rhinitis, is a protein deamidase that activates the alpha subunit of heterotrimeric G proteins. Initial activation of G alpha-q-coupled phospholipase C-beta-1 signaling by PMT is followed by uncoupling of G alpha-q-dependent signaling, causing downregulation of downstream calcium and mitogenic signaling pathways. Here, we show that PMT decreases endogenous and exogenously expressed G alpha-q protein content in host cell plasma membranes and in detergent resistant membrane (DRM) fractions. This membrane depletion of G alpha-q protein was dependent upon the catalytic activity of PMT. Results indicate that PMT-modified G alpha-q redistributes within the host cell membrane from the DRM fraction into the soluble membrane and cytosolic fractions. In contrast, PMT had no affect on G alpha-s or G beta protein levels, which are not substrate targets of PMT. PMT also had no affect on G alpha-11 levels, even though G alpha-11 can serve as a substrate for deamidation by PMT, suggesting that membrane depletion of PMT-modified G-alpha-q has specificity.